2010
DOI: 10.1007/s00508-010-1341-1
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of knee injuries and osteoarthritis in the non-dominant leg of former professional football players

Abstract: The aim of the study was to evaluate differences in knee injuries and osteoarthritis between the dominant and non-dominant legs of former professional football players. The study cohort comprised 40 retired professional players with an average age of 49.2 years. Participants completed a questionnaire about their sports and personal history with special emphasis on knee injuries/operations of the dominant and non-dominant leg. Bilateral standing knee radiographs were taken. Overall, 29 footballers (73%) had exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 29 publications
(43 reference statements)
4
64
1
Order By: Relevance
“…A typical elite European team can expect approximately 50 injuries per season including approximately 8 or 9 causing an absence of >1 month 4. Regarding players’ long-term health, former professional football players have a significant risk of developing knee osteoarthritis5 and experience a worse quality of life with regard to osteoarthritis regardless of the anatomical site (lower limbs, back and neck) 6 7…”
Section: Introductionmentioning
confidence: 99%
“…A typical elite European team can expect approximately 50 injuries per season including approximately 8 or 9 causing an absence of >1 month 4. Regarding players’ long-term health, former professional football players have a significant risk of developing knee osteoarthritis5 and experience a worse quality of life with regard to osteoarthritis regardless of the anatomical site (lower limbs, back and neck) 6 7…”
Section: Introductionmentioning
confidence: 99%
“…Many injuries can have long-lasting consequences for the injured player, such as pain and symptoms of common mental disorders [12,14]. This thesis, however, also suggests that there are other consequences of injury occurrences that are related to the performance of the team.…”
Section: Risk Tolerance In Professional Footballmentioning
confidence: 97%
“…It has been shown that professional football is associated with a more than 1000-fold higher injury rate than other professions often considered to be high risk, such as manufacturing and construction [11]. It has also been shown that 60% of retired football players have ended their careers due to injury [12].…”
Section: The Health Paradox In Sportsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies also compared a single-leg hop for the differences in kinematics and reported a significant risk of knee injuries with preponderance in the non-dominant leg (Krajnc et al, 2010;van der Harst et al, 2007). The maintenance of balance is influenced by a range of several sensorimotor functions, including muscular strength, proprioception, and the visual and A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 5 vestibular sensory systems (Brumagne et al, 2008a;Treleaven, 2008;Vaugoyeau et al, 2008).…”
Section: Introductionmentioning
confidence: 97%